2014
DOI: 10.1103/physrevb.89.035402
|View full text |Cite
|
Sign up to set email alerts
|

Raman excitation profile of theGband in single-chirality carbon nanotubes

Abstract: We present in this work measurements of the Raman excitation profile of the high-energy phonons (G band) in single-chirality (n,m) semiconducting single-wall carbon nanotubes using more than 70 laser excitation energies, and a theoretical description based on the third-order quantum model for Raman scattering. We show that the observed asymmetry in the G band Raman excitation profile is rigorously explained by considering all physical elements associated with Raman scattering in (n,m) carbon nanotubes, such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 16 publications
1
25
1
Order By: Relevance
“…Such a picture provides a useful basis for quantifying the magnitudes of the observed REP asymmetries. Next, we apply the third-order Raman analysis of Moura et al 17 and demonstrate that it is insufficient for modeling the observed asymmetries in the armchair data. We finish with a description of how the nonCondon model may be translated to a condensed-matter formalism in which phonon-mediated mixing of excitonic states is shown to be a viable route for introducing the asymmetric behavior.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Such a picture provides a useful basis for quantifying the magnitudes of the observed REP asymmetries. Next, we apply the third-order Raman analysis of Moura et al 17 and demonstrate that it is insufficient for modeling the observed asymmetries in the armchair data. We finish with a description of how the nonCondon model may be translated to a condensed-matter formalism in which phonon-mediated mixing of excitonic states is shown to be a viable route for introducing the asymmetric behavior.…”
Section: Resultsmentioning
confidence: 99%
“…We begin here a comparison of two such potential approaches. The first is an application to our data of the third-order, non-excitonic description put forward by Moura et al 17 . The second incorporates non-Condon effects into a condensed matter formalism via the introduction of a state-mixing description.…”
Section: B Evaluation Of Third-order Non-excitonic Quantum Model Fmentioning
confidence: 99%
See 3 more Smart Citations